Swamedikasi Tanaman Obat Keluarga (Toga) Bawang Merah, Bawang Putih, Jahe dan Jeruk Nipis di Desa Maku Kecamatan Dolo, Kabupaten Sigi, Sulawesi Tengah - Muthmainah Tuldjanah; Rezky Yanuarty; Aprilia Theodora (Yayasan Daarul Huda Kruengmane, 2023)
Maku Village is a village that has fertile soil and is one of the villages that produces useful plants such as shallots, garlic, ginger, lime etc. When viewed from the potential of fertile soil, this village can be used as a center for producing family medicinal plants (TOGA). The purpose of this activity is to make people more familiar with local plants that can be used as medicine. In addition to helping the Maku village community to self-medicate by becoming more familiar with the properties and methods of processing shallots, garlic, ginger and lime for various types of diseases. the method used when conducting community service in the form of lectures on the self-medication of shallots, garlic, ginger and lime to see the participants' understanding of the material presented, the presenter distributed questionnaires for assessing the success of activities that had to be completed by the people participating in this activity. The results of this community service activity increased public knowledge about self-medication with herbs, this is in accordance with the results of the average percentage for questionnaires distributed after counseling, namely 92.5%.